Experimental Demonstration of Compact S-Band MW-Level Metamaterial-Inspired Klystron - Wang X.; Zhang X.; Zou J.; Wang S.; Huang J.; Li S.; Li Y.; Liu Y.; Hu M.; Gong Y.; Schamiloglu E.; Basu B.N.; Duan Z. (My University, 2025)
Metamaterials are artificially constructed subwavelength structures exhibiting unprecedented electromagnetic phenomena. In this letter, an S-band MW-level metamaterial-inspired klystron using all-metal complementary electric split ring resonators (CeSRRs) was realized in the experiment. The CeSRR-loaded interaction structure of the klystron developed here features a miniaturized structure, the volume of which is only about 0.44 of the conventional counterparts. The metamaterial-inspired klystron based on the interaction structure loaded with CeSRRs was designed, fabricated and assembled. Using a pencil beam with parameters of 120 kV/80 A in the hot-test, the klystron delivered the biggest output power of 5.51 MW with gain of 55.6 dB and electronic efficiency of 57.4% at 2.852 GHz. This compact metamaterial-inspired klystron has potential applications in proton therapy facilities, tokamaks for the low-hybrid wave heating, and accelerators. © 2022 IEEE.